Nitrogen and Phosphorus Dual‐doped Porous Carbon Nanosheets for Efficient Oxygen Reduction in Both Alkaline and Acidic Media. Issue 18 (24th July 2018) - Li, Rong; Li, Huinan; Long, Jilan; He, Jing; Zhang, Jimin; Zheng, Hongying; Gou, Xinglong
Abstract: Development of efficient electrocatalysts with high catalytic performance and low cost for promoting oxygen reduction reaction (ORR) in both alkaline and acidic media is highly desired yet a challenging. Here, graphene‐like nitrogen and phosphorus dual‐doped porous carbon nanosheets are prepared by calcinating a homogeneous mixture of glucose, melamine and phosphoric acid with montmorillonite as the nanoreactor. The as‐prepared N, P dual‐doped porous carbon nanosheets show satisfactory ORR catalytic performance in both alkaline and acidic media due to the synergistic effect of N, P dual‐doping, abundant micro‐/meso‐pores and large specific surface area (835.91 m 2  g −1 ). Its catalytic activity in 0.1 M KOH outperforms the bench‐mark Pt/C catalyst with more positive half‐wave potential and larger diffusion current density; its catalytic activity in 0.1 M HClO4 is comparable to that of Pt/C. Furthermore, it exhibits excellent tolerance towards methanol crossover and long‐term stability, showing great promise as an alternative to Pt/C for application in fuel cells and metal‐air batteries. Abstract : Carbon‐based electrocatalysts: Graphene‐like N, P−Co‐doped porous carbon nanosheets (N, P−CS) with large surface area and high doping level of N and P were prepared by pyrolysis of homogenous mixture of glucose, melamine, phosphoric acid and montmorillonite (Glu−MA−PA−MMT). They exhibited excellent catalytic performance towards oxygen reduction in both alkaline and acidic media.